Pengaruh Struktur Audit, Konflik Peran, Ketidakjelasan Peran, dan Komitmen Organisasi terhadap Kinerja Auditor - Nanda Elfianita Ramadhani (JIATAX (Journal of Islamic Accounting and Tax), 2021)
This study aims to obtain empirical evidence of the effect of audit structure, role conflict, role ambiguity, and organizational commitment on auditor performance. The subjects in this study are auditors who work at KAP in Java and Bali and are registered with IAPI. The method used is purposive sampling. The number of questionnaire data used in this study was 40 data. The analysis used in this study is multiple linear regression analysis. The results obtained in this study are audit structure has no effect on auditor performance, role conflict and organizational commitment have a positive effect on auditor performance, and role ambiguity has a negative effect on auditor performance.